2021
DOI: 10.1097/01.aoa.0000732532.96202.8a
|View full text |Cite
|
Sign up to set email alerts
|

Causal Genetic Variants in Stillbirth

Abstract: (N Engl J Med. 2020;383:1107–1116) Between 25% and 60% of stillbirth cases are unexplained. Exome sequencing has been used to determine the cause of disease, especially in childhood disorders and fetal structural anomalies. There is an opportunity to further apply clinical exome sequencing to investigating the cause of stillbirth. Previous studies on this topic have been small, concentrated on predetermined causes, and used data from early miscarriages. This study aimed to evaluate the diagnostic uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…31 Stanley and colleagues performed whole exome sequencing in a large stillbirth case cohort and identified previously unknown genetic variants leading to a suspected genetic cause of death in 18% of the stillbirths in the study cohort. 4 They found variants in genes that are known to be pathogenic in postnatal life but also variants that are critical for in utero survival that had not yet been reported in association with stillbirth. 4 Our study contributes new data as the largest and most comprehensive intergenerational study of stillbirth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…31 Stanley and colleagues performed whole exome sequencing in a large stillbirth case cohort and identified previously unknown genetic variants leading to a suspected genetic cause of death in 18% of the stillbirths in the study cohort. 4 They found variants in genes that are known to be pathogenic in postnatal life but also variants that are critical for in utero survival that had not yet been reported in association with stillbirth. 4 Our study contributes new data as the largest and most comprehensive intergenerational study of stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…4 They found variants in genes that are known to be pathogenic in postnatal life but also variants that are critical for in utero survival that had not yet been reported in association with stillbirth. 4 Our study contributes new data as the largest and most comprehensive intergenerational study of stillbirth. It is the first to identify familial aggregation of stillbirth and quantifies stillbirth risk based on an individual's family history.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 In stillbirths, you are probably familiar with a recent paper from New York where nearly every variant was dominant, again the complete opposite of the pattern we had observed in our consanguineous population, which is in a way a silver lining because we are able to trace the cause of death in the DNA of the parents when we have no DNA left from the stillbirth (molecular autopsy by proxy). 4,5 In male infertility, we have conducted the largest genomic investigation into azoospermia and found that >80% of hits are recessive, and it will be interesting to see what similar studies in outbred populations will show as these become available. 6 In consanguineous unions, not only do you get enrichment for even the rarest of autosomal recessive traits, but you also get to map the causal variant readily even when you have no clue what the gene's function is thanks to the autozygome.…”
mentioning
confidence: 99%